Generation control of isolated small hydro power plant by using DECSA optimized FPI controller. (8th December 2020) - Nayak, Jyoti Ranjan; Shaw, Binod; Dewangan, Neeraj Kumar
Abstract : Purpose: In this work, generation control of an isolated small hydro plant (SHP) is demonstrated by applying optimal controllers in speed governor and hydraulic turbine system. A comparative analysis of application of fuzzy PI (FPI) and PID controller is conferred for generation control (both power and terminal voltage) of an SHP. The controllers are designed optimally by using crow search algorithm (CSA) and novel hybrid differential evolution crow search algorithm (DECSA). The purpose of this paper is to settle the voltage and real power to improve the quality of the power. Design/methodology/approach: In this work, the controllers (PID and FPI) are implemented in speed governor and excitation system of SHP to regulate power and terminal voltage. Differential evolution and CSA are hybridized to enhance the performance of controller to refurbish the power and terminal voltage of SHP. Findings: The proposed DECSA algorithm is applied to solve ten benchmark functions, and the effectiveness of DECSA algorithm over CSA and DE is demonstrated in terms of best value, mean and standard deviation. CSA and DECSA algorithms optimized controllers (PID and FPI) are used to design SHP with the capability to contribute power and voltage of better quality. The comparative analysis to substantiate the competence of DECSA algorithm and FPI controller is demonstrated in terms of statistical measures of power and voltage of SHP. Robustness analysis is performed by varying all system parameters to prove the effectiveness of the proposed controller. Originality/value: The proposed algorithm and FPI controller are applied individually to improve the quality of the power of SHP. DE, CSA and DECSA algorithms are implemented to solve benchmark equations. The solutions of all benchmark equations contributed by DECSA algorithm is converged rapidly and having minimum statistical measures as compared to DE and CSA algorithms. The DECSA algorithm and FPI controller are proposed with superior competence to enhance the generator performances by conceding undershoot, overshoot and settling time of power and terminal voltage. DECSA-based FPI controller contributes a noticeable improvement of the performances over other approaches.